Pengaruh Desentralisasi dan Karakteristik Informasi Akuntansi Manajemen terhadap Kinerja Manajerial - Wuryani, Eni; Djati, S. Pantja (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2007)
Business emulation facing by the company progressively tightens, require lo improve the efficiency and effectiveness of managerial performance. Existence of decentralization and characteristic of accounting information management the best can improve the managerial performance. This research check the influence decentralize and characteristic of accounting information management to managerial performance.